Evaluasi Kapasitas Sungai Kuning dalam Mengalirkan Banjir Lahar Dingin Pasca Erupsi Merapi Tahun 2010 - Rizaldi Wisnu Nugroho; Yadi Suryadi; Faizal Immaddudin Wira Rohmat; Ulin Nurul 'Aini (Journal on Education, 2024)
Indonesia as a country with the largest number of volcanoes in the world, Mount Merapi which is one of the most active. OIne of its largest eruptions recorded in 2010. Kuning River, which originates into Mount Merapi is affected by cold lava flows. In the research region, there are ten sabo dams that function as cold lava controller, supposedly designed with a 100-year return for volcanic areas. This research focuses on the capacity of rivers and sabo dams to cope with cold lava with return period of 2 to 100-year. Hydraulic modeling of cold lava was performed using non-Newtonian 2D HEC-RAS with DEM data from LiDAR in 2012. Results showed the river was able to flow lava floods 2 to 100-year return period without sabo dams. However, in existing conditions with ten sabo dams, there is flood at upstream of Sabo Dam KU-Rejodani starting from the 5-year return period. This has been validated with calculations that are in line with hydraulic simulation results. To increase river capacity, construction of 1.5-meter high embankment upstream of the KU-Rejodani sabo dam proved to be an effective solution, to increase river capacity up to Q100. This effort supports mitigation for cold lava disaster.